Opinion Of Disabled Women Students Towards Inclusive Education In Relation To Mental Health At School Level - Latha, K.; Vakkil, Dr.M. (The journal of contemporary issues in business and government, 2021)
Inclusive education acknowledges that individual students differ in their abilities and support that each student receives quality education irrespective of their abilities, disabilities, ethnicity, gender and age. In India generally students without disabilities are sent to regular schools and with disabilities are sent to special schools. At present efforts are being made to make education inclusive in nature. Inclusive education means that all children, regardless of their strength or weaknesses are accommodated in a school and become part of the same school community. Inclusive and quality education for everyone is a fundamental human right acknowledged by international nongovernmental organizations and governments that, through policies and conventions, intend to make sure that all students, especially vulnerable populations, like students with disabilities, have access to compulsory primary education (UNESCO, 2005). Since people in students’ environment can significantly influence the process of inclusion in regular schools, disabled women students and their perceptions with special abilities are recognized as playing a key role. Normative Survey method was adopted for this study. The sample consists of 142 disabled women students from Salem, Districts in Tamilnadu. The investigator used purposive sampling technique for selecting the sample from the population. The data were analyzed by descriptive and differential analyses. The major finding of this study revealed that the women disabled students have average opinion and below average mental health towards the inclusive education.